(untitled) (ҚазҰУ хабаршысы. Экономика сериясы, 2020)
A high rate of return on the investment is crucially dependent on rational investment decision making because rational investment decision ensures the successful return of an investment, especially in stocks. Investment decision making is affected by many factors; most of them are related to psychological and behavioural. Since it is difficult to make rational decisions about investment, researchers are trying to discover the factors that influence the investor’s behaviour about decision making. For the rational estimation of success rate in stocks, investors have tried many traditional methods but reached on unsatisfactory results. However, Behavioral Finance has addressed this issue and discovered the most crucial factors that may affect the investment decision making. Thus, this study aims to evaluate the influence of the factors of behavioural finance that affect decision making in the stock exchange. Three factors have been selected and used to gauge the impact on investment decision making. These factors include; overconfidence bias, representativeness bias, and availability bias. A structured close-ended questionnaire has been used to collect the data, and data was collected from 211 respondents who are investors on Karachi stock exchange. To analyze the collected data, multiple linear regression (MLR) model has been used. The result of this study shows that all three independent variables have a significant impact on investment decision making. Moreover, the relationship is positive between the independent and dependent variables. Therefore, it can be concluded that the null hypothesis is rejected. This study will assist investors to make decisions rationally in the stock market.